2018
DOI: 10.1109/mci.2018.2840738
|View full text |Cite
|
Sign up to set email alerts
|

Recent Trends in Deep Learning Based Natural Language Processing [Review Article]

Abstract: Deep learning methods employ multiple processing layers to learn hierarchical representations of data, and have produced state-of-the-art results in many domains. Recently, a variety of model designs and methods have blossomed in the context of natural language processing (NLP). In this paper, we review significant deep learning related models and methods that have been employed for numerous NLP tasks and provide a walk-through of their evolution. We also summarize, compare and contrast the various models and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
1,438
0
41

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 2,730 publications
(1,483 citation statements)
references
References 164 publications
4
1,438
0
41
Order By: Relevance
“…Another factor we use is the attention mechanism. In recent years, attention has emerged out as a widely used and important tool in field of deep learning . Attention can be defined as a vector derived as output of dense layer of network using the softmax function.…”
Section: Our Methodsmentioning
confidence: 99%
“…Another factor we use is the attention mechanism. In recent years, attention has emerged out as a widely used and important tool in field of deep learning . Attention can be defined as a vector derived as output of dense layer of network using the softmax function.…”
Section: Our Methodsmentioning
confidence: 99%
“…Once again, machine learning algorithms could help – this time by facilitating the extraction and structuring of useful clinical information from unstructured EHR data as part of a natural language processing (NLP) system or image recognition task, a task we refer to as ‘information extraction’. In fact, modern deep learning methods are revolutionizing the way computers analyze human language, producing impressive results on a variety of NLP tasks in many domains (26). …”
Section: Setting the Stage: The Two Dimensions Of A Health Outcomementioning
confidence: 99%
“…For this NLP task, the authors represented the text in each document using the classic ‘bag of words’ technique to transform the document into a structured, machine-readable format, which was then used as input to either a logistic regression model or support vector machine. This process of extracting terms from unstructured text to create features or inputs for shallow machine learning models such as support vector machines or logistic regression is a popular approach that has been used for decades to tackle NLP problems (26, 33). When the authors assessed the performance of their algorithms on test sets from four different medical sites, they found that the support vector machine (trained using a cost-sensitive classification approach (34) to maximize sensitivity) consistently achieved the best discrimination, with an area under the receiver operating characteristic curve (AUC) ranging from 0.95 to 0.98 across the four sites.…”
Section: The Four Scenariosmentioning
confidence: 99%
See 1 more Smart Citation
“…For some health-related topics, there also exists the unbalanced class distribution issues (certain classes are much more frequent than other classes), which can further erode the performance of NLP models [10,13]. To improve the performance on health-related Twitter datasets, substantial time and effort on feature engineering [17,18] is needed for the conventional machine-learning algorithms, including Support Vector Machines (SVM), K-nearest Neighbors(KNN), etc.…”
Section: Introductionmentioning
confidence: 99%